2005
DOI: 10.1111/j.1708-8240.2005.tb00466.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect on Enamel Microhardness of Two Consumer-Available Bleaching Solutions When Compared with a Dentist-Prescribed, Home-Applied Bleaching Solution and a Control

Abstract: With numerous consumer-available bleaching products on the market, it is crucial to be judicious in their selection and use. The results of this in vitro study showed that the consumer-available, paint-on bleaching solutions adversely affected enamel microhardness at some time during the study. Consumers should be made aware of this effect on enamel.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 17 publications
1
7
0
Order By: Relevance
“…In recent studies on the effect of bleaching agents on surface microhardness and morphology of enamel (5, 23, 24), specimens have been stored in artificial saliva at 37°C during the course of the study, although other studies did not use saliva as a storage medium (25–27).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent studies on the effect of bleaching agents on surface microhardness and morphology of enamel (5, 23, 24), specimens have been stored in artificial saliva at 37°C during the course of the study, although other studies did not use saliva as a storage medium (25–27).…”
Section: Discussionmentioning
confidence: 99%
“…10Ca 2þ þ6HPO 2À 4 þ2H 2 O Quantification of the phosphate group in hydroxyapatite is therefore a good indicator of the degree of mineralization of enamel. In recent studies on the effect of bleaching agents on surface microhardness and morphology of enamel (5,23,24), specimens have been stored in artificial saliva at 37°C during the course of the study, although other studies did not use saliva as a storage medium (25)(26)(27). Artificial saliva contains phosphate, which will have the potential effect of reversing the effect caused by the bleaching gels.…”
Section: Discussionmentioning
confidence: 99%
“…This result seemed to indicate that the cause of reduced bond strength was due to the oxygen ions produced by the bleaching agent. On the other hand, there were reports that claimed that the cause of reduced bond strength of resin materials was not oxygen ions, but the softening of the tooth structure caused by bleaching [30][31][32] . In this study, the specimens used for the bond strength test failed within the bonding agent layer, whether the tooth surface was bleached or not.…”
Section: Discussionmentioning
confidence: 99%
“…It is known that some mouth rinses showed efficacy when used as bleaching agents as described by Torres et al [4] and Lima et al [2]; however, the daily contact of such products for a long period of time without professional supervision can promote changes in the surface of the tooth enamel. The implication of continuous or prolonged use of mouth rinse is still controversial; studies suggest that continuous use can cause changes in the surface of the tooth enamel [2,5,9,10], while there are authors [8] who did not find significant alterations in human tooth enamel subjected to mouth rinse by simulating a daily application period with cycles of immersion times and intervals different than those indicated by the manufacturers and that correspond to daily clinical practice. Furthermore, patients have been increasingly concerned about more effective oral hygiene habits; the use of chemical control agents (i.e., mouthwash) has been adopted to complement tooth brushing and flossing.…”
Section: Introductionmentioning
confidence: 99%
“…An investigation has shown that when enamel is exposed to an inorganic aqueous solution that is unsaturated in relation to hydroxyapatite and fluorapatite, the enamel surface is altered in that a microlesion forms that is microscopically similar to the erosion that is naturally develops in the oral cavity [11]. Thus, the indiscriminate use of mouthwash, even for different purposes, may cause morphological changes on the surface of the enamel [2,[9][10][11][12][13] and result in unexpected and unwanted consequences to the dental structure.…”
Section: Introductionmentioning
confidence: 99%